PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII2 SMP NEGERI 36 PEKANBARU - Annisa Zakiya; Armis '; Titi Solfitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is a classroom action research that aims to improve learning process and increase the mathematic learning outcomes by implying Problem Based Learning model. The subject of this research is the student of VIII2 SMP Negeri 36 Pekanbaru on odd semester of 2015/2016. There are 38 students in the class, consist of 20 boys and 18 girls who have heterogeneous academic ability. This research have two cycles, each have four stages: planning, implementation, observation, and reflection. Each cycles ended by daily examination. The data of teacher and student’s activities collected by observation and analised by narrative descriptive. The data of student’s mathematic learning outcomes collected by examination and analised by descriptive statistics. The implementation called success if there’s positive improvement of the learning process and the number of students who reach minimum completeness criteria increase after the implementation. The result shows that the implementation of the learning process at the second cycle have been improve from the implementation at the first cycle. The weakness at the first cycle has been improved by implementation at the second cycle according to improvement plan after reflection at the first cycle. More than half students actively participated in the learning process, as in group discussion, presented their works, responded to other group, and sum up the learning conclusion. The number of students who reach minimum completeness criteria increase from 36.84% at the base score to 55.26% at the first cycle and 71.05% at the second cycle. Therefore, it can be said that there is an improvement of learning process and mathematic learning outcomes after the implementation. This research conclude that implying Problem Based Learning model can improve learning process and increase mathematic learning outcomes for students of VIII2 SMP Negeri 36 Pekanbaru on odd semester of 2015/2016.